Antioxidant activity of ginger extract (zingiber officinale) in soybean oil under thermoxidation - Jorge, Neuza [UNESP]; Andreo, Denise [UNESP] (Emerald, 2013)
Purpose: The purpose of this paper is to evaluate the antioxidant activity of ginger ethanol extract in soybean oil under thermoxidation. Design/methodology/approach: A total of four treatments were used: soybean oil free of synthetic antioxidants, soybean oil containing 2,500 mg/kg of ginger extract, soybean oil containing 50 mg/kg of TBHQ, soybean oil containing the mixture of natural extract, and TBHQ in the before-cited concentration. The treatments were discontinuously submitted to plates heated at 180°C, for 20 hours. Samples were removed in the times of 0, 4, 8, 12, 16 and 20 hours of heating and they were analyzed as to their oxidative stability, total polar compounds, peroxide and conjugated diene values. Findings: The results showed the efficiency of the ginger extract in protecting the oil against lipid oxidation. It could be concluded that ginger extract might be indicated as an additive that acts against lipid oxidation and, consequently, increases shelf life of food. Practical implications: These studies may prove to be beneficial to the exploitation of natural antioxidant sources for the preservation and/or extension of raw and processed food shelf life. Therefore, they could also be applied in the area of pharmaceuticals for the protection of human life. Originality/value: This study offers information on the use of natural antioxidants as an alternative to the use of synthetic antioxidants, which might be considered toxic. © Emerald Group Publishing Limited.
Keywords: Chemical properties of materials; Ethanol extract; Food products; Lipid oxidation; Soybean oil; Glycine max; Zingiber officinale